The importance of learning in aesthetic surgery during plastic surgery residency - Ramirez, Oliver René; Flores, Emmanuel A.; Gracida, Noe I.; Grau, Karla F.; Sánchez, Jazmin Villasana; Azcúe, Arsenio F. Araujo; Piña, Raymundo Torres (International Journal of Research in Medical Sciences, 2024)
Given the challenges and the long journey that every plastic surgeon undergoes, it is commendable to witness the training received by residents in plastic and reconstructive surgery in aesthetic procedures (body contouring, breast augmentation, mastopexy, rhinoplasty, facelift, blepharoplasty) during their final year of training at a tertiary institution in a country like Mexico. It is important to verify whether they develop optimal and comprehensive training to face their professional lives. The number of aesthetic surgeries performed by 12 residents during their final year of plastic surgery training was captured from clinical records for the years 2022 and 2023. The data were compiled into a database using Microsoft excel V16.47.1 and subsequently analyzed using statistical package for social sciences (SPSS) software, v23.0. Significant differences were found among residents (p value=0.02) regarding the number of procedures performed by each one. However, according to the presented diagnoses, each resident faces the same cases, which are the most requested in Mexico and worldwide. This review study concludes that final-year residents in plastic surgery undergo training adhering to the academic program established by the PUEM, performing the most common aesthetic procedures in Mexico and worldwide according to the diagnoses presented by each resident.